Habitat associations of four ungulates in mountain forests of southwest China, based on camera trapping and dung counts data. Issue 1 (8th October 2013) - Li, Xueyou; Buzzard, Paul; Jiang, Xuelong
Abstract: The present study aimed to assess abundance indices and habitat associations of four sympatric ungulate species (alpine musk deer Moschus chrysogaster, tufted deer Elaphodus cephalophus, Chinese serow Capricornis milneedwardsii, and Chinese goral Naemorhedus griseus ) in Baima Xueshan Nature Reserve of southwest China, using camera trapping and dung counts data. Camera traps were set along six dung transects in different habitats and explored habitat use of the sympatric ungulates using trapping rates. The results obtained revealed that Chinese serow showed a negative association with open canopy cover and low canopy cover. Alpine musk deer were associated with oak shrubs, oak forests and open canopy cover, while tufted deer avoided oak shrubs. Goral showed no significant associations with habitat variables. Alpine musk deer and tufted deer had considerable habitat overlap with Chinese serow. By finding a high correlation between indices, the study indicates that camera trapping may represent a valid index of relative abundance, matching results from other studies.